Optimal timing of laparoscopic cholecystectomy after endoscopic retrograde cholangiopancreatography - Sahoo, Rasmiranjan; Samal, Debasish; Pradhan, A.; Sultana, Rima; Nayak, Nabakishore; Padhy, Rabindra Nath (International Surgery Journal, 2017)
Background: Nowadays in patients with cholelithiasis with choledocholithiasis, the ideal treatment is endoscopic retrograde cholangiopancreatographic (ERCP) removal of duct stone and laparoscopic cholecystectomy. But when to do and whether we can do it simultaneously or one after another and what interval should be there, that is always controversial. The purpose was an optimal gap for cholecystectomy after ERCP. Methods: We have done a comparison study in 60 patients within a duration of 2 year who had already done ERCP. Group 1, those patients who had laparoscopic cholecystectomy within 72 hours compared with group 2 who had laparoscopic cholecystectomy after an interval of 6 week. Primary outcome was the conversion rate from lap to open cholecystectomy. Secondary outcome was duration of operation, intra-operative difficulties, postoperative morbidity and hospital stay. Results: Of 60 consecutive patients 30 were in group I and 30 were in group II. There is no difference in demographics, laboratory or ultrasonographic findings. The hospital stays in group I is significantly shorter than group II and conversion rate; operative time is higher in group II. No statistically significant difference in post-operative morbidity between both groups. Conclusions: Early laparoscopic cholecystectomy within 72 hr is better than interval (6 week) cholecystectomy after ERCP with shorter hospital stay and less intraoperative difficulties.